Pengaruh Kinerja Keuangan terhadap Return Saham dengan Inflasi sebagai Variabel Moderasi - Muhammad Ashim; Riana Rachmawati Dewi; Dimas Ilham Nur Rois (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study are to explore impact of current ratio variable, debt to equity ratio variable, and profit growth variable to stock returns, integrating inflation for moderating variable. The current ratio indicates a company's ability to meet short-term obligations, debt to equity ratio variable reflects the level on l, while profit growth variable is provides an overview of profitability performance. Stock returns are measured as the result of shareholder investments. Inflation is identified as a moderating variable to understand how these factors interact in the context of price instability. The study are represented by companies in the food and beverage sub-sector that listed on the IDX at the period 2019-2022. The classification method employs purposive sampling, resulting in 40 samples. The data processing for this research employs the multiple linear regression technique using SPSS version 21. The results of this study indicate that, individually, profit growth can influence stock returns. However, the other two variables do not have a significant impact on stock returns. Moreover, inflation can act as a moderator in the influence of the current ratio variable on stock returns, while inflation does not moderate the influence of the debt to equity ratio variable and profit growth variable. Keywords : Stock0Return, Current Ratio, Debt0to Equity Ratio, Profit0Growth, Inflation